(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Arsenic (As) contamination in rice (Oryza sativa L.) has become a global concern as a potential dietary risk to human health. In order to elucidate the effect of soil As contamination on rice and its management through water regimes, we analyzed two water management practices viz. alternate wetting and drying (AWD) and continuous flooding (CF) in combination with different concentration of As (0, 20 and 40 mg kg-1) using BRRI dhan47 rice variety. Pots were filled with 10 kg soil with background soil As 3.73 mg kg-1. Results showed that As contamination significantly reduced growth and yield of rice. The grain and straw arsenic concentrations were 0.55 and 17.31 mg kg-1, respectively in soil treated with As 40 mg kg-1 while 0.18 mg kg-1 grain As and 2.41 mg kg-1 straw As were found in As 0 mg kg-1 treatment. The AWD technique significantly reduced grain As concentration by 14% compared to CF with significant increase in grain yield. Straw As concentration, grain As uptake, and total As uptake were also significantly reduced by AWD practice. Thus, AWD rice cultivation can be a potential and sustainable technology to mitigate arsenic problem in rice in As-contaminated areas. J Bangladesh Agril Univ 18(3): 545–550, 2020 https://doi.org/10.5455/JBAU.103559